Widen your horizons! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Agricultural information resource centers : A world directory 2000 (CD-ROM) compiled by IAALD, National Information Services Corporation, USA. 2000. CTA Number 1040. 80 credit points